Quispe-Agnoli, R. y Brian, A. (ed.) (2022). "Latin American Literature in Transition Pre 1492-1800". Cambridge: Cambridge University Press. - Esther Soro Cuesta (América sin Nombre)
Reseña del libro Quispe-Agnoli, R. y Brian, A. (ed.) (2022). Latin American Literature in Transition Pre 1492-1800. Cambridge: Cambridge University Press, 385 pp, ISBN: 9781108976893.